AUTOMATED ELECTRICAL SYSTEMS OF ROBOTICS AREAS OF APPLICATION OF PROCEDURES - Rakhmatali Meliboyev Inomjonovich; Otaqo‘ziyeva Bashoratkhan Nabikoziyevna; Usmanova Firuza Bakhodirjonovna (American Journals Publishing, 2023)
This article provides information on the areas of application of automated electrical systems of robotics and the use of automated electrical equipment in the textile and manufacturing industries.
Keywords: Automation, Robotics, technician, product, textile, textile.